Progressive anemia of prematurity is associated with a critical increase in cerebral oxygen extraction. (January 2020) - Whitehead, Halana V.; Vesoulis, Zachary A.; Maheshwari, Akhil; Rambhia, Ami; Mathur, Amit M.
Abstract: Background: Elevated cerebral fractional tissue oxygen extraction (cFTOE) is an adaptation to anemia of prematurity (AOP). cFTOE ≥0.4 is associated with brain injury in infants ≤30 weeks. This longitudinal study sought to investigate the utility of cFTOE in the evaluation of AOP. Methods: Infants ≤30 weeks estimated gestational age (EGA) underwent weekly hemoglobin, cerebral saturation, and pulse oximetry recordings from the second through 36 weeks post-menstrual age (PMA). Recordings were excluded if they were under 1 h or if hemoglobin was not measured within 7 days of recording. Mean cFTOE was calculated for each recording. Statistical analysis used linear mixed-effects modeling and receiver operating characteristic analysis. Results: 144 recordings from 39 infants (mean EGA 27.6 ± 2.2 weeks, BW 1139 ± 286 g) were included of whom 39% (15/39) were transfused. The mean recording length was 2.8 ± 1.3 h. There was a significant negative correlation between hemoglobin and cFTOE ( R = −0.423, p ≤.001). In a multivariate model, adjusting for EGA, PMA, and patent ductus arteriosus treatment the AUC was 0.821. A critical increase in cFTOE occurred at a hemoglobin level of 9.6 g/dL. Conclusions: AOP is associated with a critical increase in cFTOE that occurs at a significantly higher hemoglobin level than standard clinical thresholds for transfusion. Highlights: cFTOE, derived from regional cerebral saturations measured using NIRS and pulse oximetry, is a marker of regional tissue oxygen delivery and metabolic activity. Elevated cFTOE is a known adaptation to anemia, but values ≥0.4 are associated with brain injury in preterm infants. Current clinical threshold hemoglobin levels for pRBC transfusions in anemia of prematurity are population based and not based on individual patient physiology. This study identified the threshold for critical oxygen extraction (cFTOE ≥0.4) as 9.6 g/dL in stable preterm infants with anemia of prematurity, significantly higher than current thresholds for transfusion (<8 g/dL). Longitudinal evaluation of premature infants using concurrent hemoglobin levels and cerebral NIRS may help define patient specific transfusion thresholds of hemoglobin in preterm infants.